FATIGUE SIMULATION OF TWIST BEAM BASED ON MEASURED LOAD SPECTRUM - ZHAN Nan; ZHENG FuRong; GAO PengFei; HAN Li (Jixie qiangdu)
Base on six component test system,the load spectrum of a certain type of car were obtained in skid pad.As the input data,the fatigue of the twist beam was analyzed by the use of multiple computer aided engineering（ CAE） as finite element method,Multi-body dynamics and fatigue analysis.The risk of the cracking position was predicted and contrasted with the road test.The results show that the predicted damage position based on the measured load spectrum was in good consistence with the road test.For the cracking risk position,corresponding optimized scheme was presented,and the damage distribution after optimization was given.The optimized scheme effectively reduced the risk of cracking of the original scheme,and the cracking problem of the twist beam was solved.